Pentingnya Restoratif Justice dalam Hukum Pidana Indonesia - Wibawa, Sholeh Nur; Irawan, Andrie; Fatmawati, Fifi (CV. Kurnia Grup, 2024)
The state of Indonesia is a state of law, an affirmation of this can be seen in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Settlement of cases through the judicial system which leads to a court verdict means an enforcement of the rules towards the slow lane. This is because law enforcement goes through a long distance, through various strata ranging from the Police, Prosecutors, District Courts, High Courts and even to the Supreme Court which ultimately has an impact on the accumulation of problems that are not small in number in the Court and not to mention other impacts. For this reason, it is necessary to continue with steps to draft laws concerning the rights and basic obligations of the state community in the context of practicing Pancasila and the 1945 Constitution. The reform of the Criminal Code which was drafted is positioned as laying the foundation for the building of the national criminal law system. Regarding the Politics of the Criminal Code, there is a concept known as the concept of Restorative Justice in the upcoming National Criminal Code. Restorative justice includes restoring the relationship between the victim and the perpetrator. The restoration of this correlation can be based on a common convention between the victim and the perpetrator. The victim can provide information about the loss suffered and the perpetrator is also given the opportunity to make amends, trough procedures for compensation, reconciliation, social work, as well as other conventions.